Roles of transducin-like enhancer of split (TLE) family proteins in tumorigenesis and immune regulation - Yu, Guiping; Chen, Yiqi; Hu, Yuwen; Zhou, Yan; Ding, Xiaoling; Zhou, Xiaorong (Frontiers in Cell and Developmental Biology, 2022)
Mammalian transducin-like enhancer of split family proteins (TLEs) are homologous to Drosophila Groucho (Gro) and are essential transcriptional repressors. Seven TLE family members, TLE1-7, have been identified to date. These proteins do not bind DNA directly; instead, they bind a set of transcription factors and thereby inhibit target gene expression. Loss of TLEs in mice usually leads to defective early development; however, TLE functions in developmentally mature cells are unclear. Recent studies have revealed that TLEs are dysregulated in certain human cancer types and may function as oncogenes or tumor suppressors in different contexts. TLE levels also affect the efficacy of cancer treatments and the development of drug resistance. In addition, TLEs play critical roles in the development and function of immune cells, including macrophages and lymphocytes. In this review, we provide updates on the expression, function, and mechanism of TLEs; discuss the roles played by TLEs in tumorigenesis and the inflammatory response; and elaborate on several TLE-associated signaling pathways, including the Notch, Wnt, and MAPK pathways. Finally, we discuss potential strategies for targeting TLEs in cancer therapy.